How to stimulate employees’ innovative behavior: Internal social capital, workplace friendship and innovative identity - Zhao, Xiaoyang; Yi, Changjun; Chen, Chusheng (Frontiers in Psychology, 2022)
With the digital transformation of the economy and the rise of community innovation, how to stimulate employees’ innovative behavior becomes the basis for building sustainable competitive advantage in organizations. However, research has yet to systematically investigate the effect of internal social capital on employees’ innovative behavior. Based on social identity theory and resource conservation theory, this paper constructs a model to explain the mediating role of innovative identity between internal social capital and employees’ innovative behavior and the moderating role of workplace friendship. Using SPSS 27 and Amos 24 to analyze the data of 284 questionnaires, the results show that (1) internal social capital has a positive effect on employees’ innovative behavior, (2) innovative identity plays a partial mediating effect in the relationship between internal social capital and employees’ innovative behavior, and (3)workplace friendship has a positive moderating effect on the relationship between internal social capital and employees’ innovative behavior. The conclusion provides management insight sand practical guidance for creating an internal organizational climate to promote employees’ innovative behaviors.